ChatGPT, napiši nama članek o možnostih uporabe umetne inteligence v visokošolskem izobraževanju - Pavlin, Samo (Teorija in praksa, 2024)
This article explores how generative artificial intelligence (GenAI) can assist with the development of students through enhanced learning, creative thinking, and teamwork. We begin by examining the advent of GenAI from the perspective of the traditional role held by higher education. This is followed by a presentation of selected views on knowledge and learning, emphasising the role of GenAI in informal learning, creativity, knowledge creation, and collaborative learning and teamwork. These processes are complemented by the perspectives of multimedia technology, meta-learning, and the functioning of communities of practice. Building on the analysis, we develop a conceptual model for examining potential uses of GenAI in higher education. The introductory and concluding dis cussions are situated in the context of the knowledge society
Keywords: academic learning; competencies; družba znanja; generative artificial intelligence; Generativna umetna inteligenca; higher education; knowledge based society; kompetence; Umetna inteligenca; visoko šolstvo; visokošolsko učenje; Vzpodbujevalno učenje (umetna inteligenca)